Kierkegaard a biography - Hannay, Alastair (Cambridge University Press, 2001)
Written by one of the world's preeminent authorities on Kierkegaard, this 2001 biography was the first to reveal the delicate imbrication of Kierkegaard's life and thought. To grasp the importance and influence of Kierkegaard's thought far beyond his native Denmark, it is necessary to trace the many factors that led this gifted but (according to his headmaster) 'exceedingly childish youth' to grapple with traditional philosophical problems and religious themes in a way that later generations would recognize as amounting to a philosophical revolution. This book offers a powerful narrative account which will be of particular interest to philosophers, literary theorists, intellectual historians, and scholars of religious studies as well as any non-specialist looking for an authoritative guide to the life and work of one of the most original and fascinating figures in Western philosophy